Given that f ( x ) = 3 x 4 , find the value of f ′ ( 2 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ′ ( x ) = 1 2 x 3 , hence f ′ ( 2 ) = 1 2 × 8 = 9 6 .
how it became 12x^3 it has to be 3x^3=3*16 =>48
Applying the power formula , we get
f ( x ) = 3 x 4
f ′ ( x ) = 1 2 x 3
f ′ ( 2 ) = 1 2 ( 2 3 ) = 1 2 ( 8 ) = 9 6
Problem Loading...
Note Loading...
Set Loading...
f(x) = 3 x 4 Given equation
f'(x) = ( 3 × 4 ) x 4 − 1 Power Rule
f'(x) = ( 1 2 ) × ( x 3 ) Simplify
f'(2) = ( 1 2 ) × ( 2 3 ) Substitution
f'(2) = ( 1 2 ) × ( 8 ) Simplify
f'(2) = 96 Simplify